Evaluasi sistem manajemen perpustakaan berbasis Cerah Informasi Pustaka (CIP) menggunakan model hot-fit di Perpustakaan Universitas Tridinanti Palembang - Arinda Dwi Putri; Sely Yoanda (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Background of the Study: Advances in information technology have transformed library services into digital systems. Tridinanti University Library has adopted the CIP system to manage collections, circulation, and member data, but evaluation is needed to ensure optimal utilization. Objectives: The aim was to evaluate the performance of CIP using the HOT-Fit model, which encompasses People, Organization, and Technology. Method: Qualitative methods with a descriptive approach were used. Data were obtained through in-depth interviews and observations of librarians and library staff as system users. Finding: From a people perspective, CIP helps speed up work and improve librarian effectiveness, but feature utilization remains low due to limited training. From an organizational perspective, the tools and work structure are supportive, but coordination, CIP usage policies, and training programs are still suboptimal. From a technological perspective, CIP is quite user-friendly and capable of displaying collection information, but challenges exist such as dependence on a central server, limited search features, and the lack of written guidelines. Conclusion: CIP has been shown to improve the quality of library services at Tridinanti University. However, its sustainability requires improvements in the form of regular training, stronger technical support, the development of user guides, and the development of features to better meet needs.